The Influence of Enterprise Risk Management (ERM) on Company Value - Karunia, Nuuruddunya; Hariyati (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of Enterprise Risk Management (ERM) on firm value. The sample consisted of companies in the transportation and warehousing, service, and food and beverage subsectors in 2023, with a total of 100 observations. Hypothesis testing used multiple regression analysis. The results indicate that ERM has a positive effect on firm value. This research has implications for companies and policies that support ERM disclosure so that it can function optimally in increasing firm value.